Measurement of [Formula: see text] production with additional jet activity, including [Formula: see text] quark jets, in the dilepton decay channel using pp collisions at [Formula: see text] - Khachatryan, V; Sirunyan, A M; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Friedl, M; Frühwirth, R; et al. (The European physical journal. C, Particles and fields, 2016)
Jet multiplicity distributions in top quark pair ([Formula: see text]) events are measured in pp collisions at a centre-of-mass energy of 8 TeV with the CMS detector at the LHC using a data set corresponding to an integrated luminosity of 19.7[Formula: see text]. The measurement is performed in the dilepton decay channels ([Formula: see text], [Formula: see text], and [Formula: see text]). The absolute and normalized differential cross sections for [Formula: see text] production are measured as a function of the jet multiplicity in the event for different jet transverse momentum thresholds and the kinematic properties of the leading additional jets. The differential [Formula: see text] and [Formula: see text] cross sections are presented for the first time as a function of the kinematic properties of the leading additional [Formula: see text] jets. Furthermore, the fraction of events without additional jets above a threshold is measured as a function of the transverse momenta of the leading additional jets and the scalar sum of the transverse momenta of all additional jets. The data are compared and found to be consistent with predictions from several perturbative quantum chromodynamics event generators and a next-to-leading order calculation.